2021
DOI: 10.1101/2021.07.26.453818
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluating Differences in Elastic Modulus of Regenerated and Uninjured Mouse Digit Bone through microCT Density-Elasticity Calculation and Nanoindentation Testing

Abstract: Bone is an essential, healing structure in vertebrates that ensures daily function. However, the regenerative capacity of bone declines with age, compromising quality of life in the elderly and increasing cost of care. Here, for the first time, the elasticity of regenerated bone in a mouse digit amputation model is evaluated in order to better investigate biomechanics of skeletal regeneration. Amputation of the distal one third of the digit (third phalangeal element P3) results in de novo regeneration of the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…By using this processing method, we found that age increases the elasticity of the distal tip of the unamputated digit, while the process of regeneration predictably decreases elasticity and hardness. Surprisingly, we found that both calculated elasticity and direct measurements of hardness show no significant difference between the 6-month-old ( Hoffseth K. et al, 2021 ) and 18-month-old mice after regeneration. These biomechanical similarities are in contrast with age-dependent differences seen in the bone architecture of young and aged mice.…”
Section: Introductionmentioning
confidence: 61%
See 4 more Smart Citations
“…By using this processing method, we found that age increases the elasticity of the distal tip of the unamputated digit, while the process of regeneration predictably decreases elasticity and hardness. Surprisingly, we found that both calculated elasticity and direct measurements of hardness show no significant difference between the 6-month-old ( Hoffseth K. et al, 2021 ) and 18-month-old mice after regeneration. These biomechanical similarities are in contrast with age-dependent differences seen in the bone architecture of young and aged mice.…”
Section: Introductionmentioning
confidence: 61%
“…Calculation of elastic modulus values utilized a processing pipeline starting with BMD as measured by μCT and using established density-elasticity relationships ( Knowles et al, 2016 ) as detailed in Hoffseth K. et al (2021) using 6-month-old mice. Mineral density values were calculated as previously described ( Hoffseth K. F. et al, 2021 ) by averaging grayscale pixel intensity using L3-sized voxels ( L = 3 pixels) for each representative data point through iterative operation over the digit image stack, reducing computation time without avoiding loss of digit characteristics.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations